Spectral investigations of CM Draconis - new results - Kuznetsov, M.K.; Pavlenko, Ya.V.; Jones, H.R.A.; Pinfield, D.J. (Advances in Astronomy and Space Physics, 2012)
CM Draconis is spectroscopic and eclipsing binary system that consists of two nearly identical M dwarfs. The masses and radii for the components are known with high accuracy. The period of the system is P = 1.268 day. In the course of this work we used 29 medium resolution (R = 47, 000) echelle spectra of CM Dra which were obtained at several different orbital phases at the 4.2-m William Herschel Telescope. We calculated synthetic spectra for a region of Nai 8185 Å, Nai 8197 Å and RbI 7818 Å lines and fitted the spectra for all of the orbital phases. We refined the effective temperature and metallicity of the system components, using similarity function (S function) of the observed and synthetic spectra for different phases.